DETERMINAN PENGANGANGGURAN TERDIDIK DI INDONESIA - Milda Rosalinda; Sry Wahyuny Mustafa; Mustafa Muhani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Unemployment is an economic problem that cannot be avoided by every country, both developed and developing countries. The main problem in unemployment is people who are highly educated but do not have jobs, causing educated unemployment. Therefore this study aims to identify the determinants of educated unemployment in Indonesia with Gross Regional Domestic Product, Regional Minimum Wage, and Foreign Investment as indicators. This research method uses a quantitative time series during 2005-2021. The data used is secondary data sourced from the Central Bureau of Statistics. The analytical method used is the Classical Assumption method. The results of the study show that partially (t-test) the GRDP and RMW variables do not have a significant effect on the level of educated unemployment in Indonesia, while Foreign Investment has a negative and significant effect on the level of educated unemployment in Indonesia. Based on the results of the simultaneous research (F-test) the variables GRDP, RMW, and Foreign InvestmentI together have a significant influence on Educated Unemployment in Indonesia in 2005-2021.